2016
DOI: 10.3389/fphar.2016.00415
|View full text |Cite
|
Sign up to set email alerts
|

Biased Agonism of Three Different Cannabinoid Receptor Agonists in Mouse Brain Cortex

Abstract: Cannabinoid receptors are able to couple to different families of G proteins when activated by an agonist drug. It has been suggested that different intracellular responses may be activated depending on the ligand. The goal of the present study was to characterize the pattern of G protein subunit stimulation triggered by three different cannabinoid ligands, Δ9-THC, WIN55212-2, and ACEA in mouse brain cortex. Stimulation of the [35S]GTPγS binding coupled to specific immunoprecipitation with antibodies against d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…For example, dopamine receptor selectivity between Ga i1 , Ga i2 , Ga i3 , Ga o , plus Gb 1 and Gg 2 has been reported using GTPgS assays (Gazi et al, 2003). Similarly, selectivity within Ga i1 , Ga i2 , Ga i3 , Ga o , Ga z , Ga q/11 , and Ga 12/13 has been reported with cannabinoid receptor agonism (Diez-Alarcia et al, 2016). Recently, the application of sensitive BRET probes to directly measure G protein activation in living cells has been applied to the measurement of G protein subunit selectivity (Lohse et al, 2012;Saulière et al, 2012).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…For example, dopamine receptor selectivity between Ga i1 , Ga i2 , Ga i3 , Ga o , plus Gb 1 and Gg 2 has been reported using GTPgS assays (Gazi et al, 2003). Similarly, selectivity within Ga i1 , Ga i2 , Ga i3 , Ga o , Ga z , Ga q/11 , and Ga 12/13 has been reported with cannabinoid receptor agonism (Diez-Alarcia et al, 2016). Recently, the application of sensitive BRET probes to directly measure G protein activation in living cells has been applied to the measurement of G protein subunit selectivity (Lohse et al, 2012;Saulière et al, 2012).…”
mentioning
confidence: 85%
“…7TMRs generally can interact with members spanning across these general groupings despite the fact that the G protein functional outcomes can be very different (Michal et al, 2007;Inoue et al, 2012;Saulière et al, 2012). For instance, cannabinoid receptors interact with Ga z , Ga q/11 , and Ga 12/13 (Diez-Alarcia et al, 2016;Laprairie et al, 2017). Ligand-stabilized receptor conformations drive the selection of G protein interactions and these selections can be discerned within G protein subunit families; for instance, studies with bioluminescence resonance energy transfer (BRET) biosensors have shown that oxytocin analogs differentiate between individual G i/o family members (Ga q , Ga i1 , Ga i2 , Ga i3 , Ga oA , Ga oB ; Busnelli et al, 2012).…”
Section: A Receptor/g Protein Interactionsmentioning
confidence: 99%
“…This procedure can mitigate concerns related to activation or inhibition of multiple G proteins and reduces the variability in sensitivity by different G proteins (Milligan, 2003; Strange, 2010). This assay has since been used to identify specific CB 1 receptor–G protein interactions (Blume, Eldeeb, Bass, Selley, & Howlett, 2015; Diez-Alarcia et al, 2016; Eldeeb et al, 2016; Erdozain, Diez-Alarcia, Meana, & Callado, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Both cannabinoid CB1R and CB2R are mainly coupled to Gi/o resulting in the inhibition of the adenylate cyclase/cAMP cascade and voltage-gated Ca2+ channels, as well as the stimulation of inwardly rectifying K+ currents, and of mitogen-activated protein kinase (MAPK) activity [18]. Interestingly, a growing amount of evidence shows that CB1R can couple with different subunits of the classic inhibitory Gi/o proteins, but also with Gαz, Gαq/11, and Gα12/13 [19,20], and that under specific circumstances, CB1R can shift toward activation of Gs and potentiation of neurotransmission [21,22]. In addition, activation of CB1R in astrocytes increases intracellular calcium probably mediated by Gq proteins [23], and in the cardiovascular system, CB1R can bind to Gs or Gq/11 to modulate vasoconstriction and hypertension [24].…”
Section: The Endocannabinoid and Orexin Systemsmentioning
confidence: 99%